Fracasso e verdade na recepção de Políbio e Tucídides - Breno Battistin Sebastiani (Humanitas Supplementum, 2017)
This book discusses the problem of the reception either of, or in, Thucydides' and Polybius' texts, examining its narrative, historiographical, literary and/or cultural perspectives. It is subdivided into eight meditations. The first meditation presents three methodological procedures (reception, mediation, comparison) which articulate the discussion about the main constituents (political failures, truths) of that problem along the other seven meditations.